Tinjauan Siyasah Dusturiyah Terhadap Pelaksanaan Asas Keseimbangan dan Profesionalitas Pelayanan Publik di Kecamatan Naringgul Berdasarkan Pasal 4 Perda Kabupaten Cianjur Nomor 6 Tahun 2013 Tentang Pelayanan Publik - Irawan, Feri; Ahmad Saebani, Beni; Alamsyah, Taufiq (LPPM Universitas Ekasakti Padang, 2024)
This study discusses the review of siyasah dusturiyah on the implementation of the principle of balance of rights and obligations, as well as the professionalism of public services based on Article 4 of Cianjur Regency Regional Regulation Number 6 of 2013 concerning Public Services. The purpose of this study is to determine the implementation of the principle of balance of rights and obligations, as well as the principle of professionalism of public services in Integrated Administrative Services in Naringgul District, to determine government policies in overcoming obstacles to Integrated Administrative Services in Naringgul District, and to determine the review of Siyasah Dusturiyah on the implementation of the principle of balance of rights and obligations, as well as the principle of professionalism of public services in Integrated Administrative Services in Naringgul District based on Article 4 of Cianjur Regency Regional Regulation Number 6 of 2013 concerning Public Services. The method used is qualitative research method with descriptive type. As for the results of this study, the implementation of Integrated Administrative Services in Naringgul District is in accordance with the concept of siyasah dusturiyah, which is to regulate the interests of the people for the achievement of benefits.